Exploring the Relationships Between Independent Listening and Listening-Reading-Writing Tasks in Chinese Language Testing: Toward a Better Understanding of the Construct Underlying Integrated Writing Tasks. Issue 3 (2nd July 2016) - Zhu, Xinhua; Li, Xueyan; Yu, Guoxing; Cheong, Choo Mui; Liao, Xian
ABSTRACT: Integrated assessment tasks have been increasingly used in language tests, but the underlying constructs of integrated tasks remain elusive. This study aimed to improve understanding of the construct of integrated writing tasks in Chinese Language examinations in Hong Kong by looking at the language competences measured in the Listening-Reading-Writing Task and how they relate to the outcome of the Independent Listening Task. The performance of 226 native Chinese Secondary Five students on both tasks were subject to correlation analysis, joint factor analysis, and regression analysis. It was found that the students' performance in the Independent Listening Task and the Listening-Reading-Writing Task was statistically significantly correlated, but the two tasks did not seem to have common factors as shown in the joint factor analysis. The indicators of elaboration, evaluation, and creation in the Independent Listening Task were significantly correlated with multiple indicators in the Listening-Reading-Writing Task, and evaluation and creation together explained 8.9% of the variance in the total score of the Listening-Reading-Writing Task. The findings support the framework (i.e., the "four pillars" of integrated writing competence) applied in public examinations in Hong Kong. They also imply that the two types of writing tasks are complementary in the assessment of Chinese Language competence.